World Bank Assistance to the Financial Sector : A Synthesis of IEG Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This report is a synthesis of three evaluations carried out by the Independent Evaluation Group and completed between July 2005 and February 2006, on different aspects of Bank assistance to financial sector development in client countries. The three evaluation reports are World Bank Lending for Lines of Credit: An Independent Evaluation Group (IEG) Evaluation; IEG Review of World Bank Assistance for Financial Sector Reform; and Financial Sector Assessment Program: IEG Review of the Joint World Bank and IMF Initiative. This paper seeks to draw out common themes and issues that have arisen from the three evaluations, which reviewed major components of the Bank's assistance during more than a decade to the financial sectors of client countries.